Pseudolinfoma cutáneo secundario a tatuaje: un caso clínico - Montiel G., Carla; Aguilera F., Camila; del Castillo P., Douglas; Vera P., Valentina; Morales H., Claudio (Revista Hospital Clínico Universidad de Chile, 2025)
Tattoos can cause various dermatological complications, such as infections, contact dermatitis, lichenoid reactions, and granulomatous reactions. It is crucial for general practitioners and dermatologists to be informed about these complications to properly prevent, recognize, and treat patients. This is a case of tattoo pseudolymphoma appearing months after the tattoo was done, in the areas corresponding to the red ink. Cutaneous pseudolymphoma is a reactive lymphocytic proliferation that mimics a cutaneous lymphoma. Although the pathophysiology is uncertain, red pigment has been associated with higher complication rates. The lack of specific regulation in Chile and contamination in tattoo inks highlight the need for better standards. The complication presents as papules and plaques that may resolve spontaneously or with treatment. Prevention is recommended through the choice of reputable tattoo artists and safe inks.